Indications of decreasing human PTS concentrations in North West Russia. - Charlotta Rylander; Torkjel M Sandanger; Natalya Petrenya; Alexei Konoplev; Evgeny Bojko; Jon Øyvind Odland (Global Health Action, 2011)
The Russian Arctic covers an enormous landmass with diverse environments. It inhabits more than 20 different ethnic groups, all of them with various living conditions and food traditions. Indigenous populations with a traditional way of living are exposed to a large number of anthropogenic pollutants, such as persistent organic pollutants (POPs) and toxic metals, mainly through the diet. Human monitoring of persistent organic pollutants (POPs) and heavy metals in the Russian Arctic has only been performed on irregular intervals over the past 15 years, thus, there is still a lack of baseline data from many ethnic groups and geographical regions. The aim of the current study was to investigate concentrations of POPs and toxic metals in three groups of indigenous people from the Russian Arctic. Plasma concentrations of POPs were measured in one of the locations (Nelmin-Nos) in 2001–2003 which gave the unique opportunity to compare concentrations over time in a small Russian arctic community.During 2009 and early 2010, 209 blood samples were collected from three different study sites in North West Russia; Nelmin-Nos, Izhma and Usinsk. The three study sites are geographically separated and the inhabitants are expected to have different dietary habits and living conditions. All blood samples were analyzed for POPs and toxic metals.PCB 153 was present in highest concentrations of the 18 PCBs analyzed. p,p′-DDE and HCB were the two most dominating OC pesticides. Males had higher concentrations of PCB 138, 153 and 180 than women and age was a significant predictor of PCB 153, 180, HCB and p,p′-DDD. Males from Izhma had significantly higher concentrations of HCB than males from the other study sites and women from Usinsk had higher concentrations of p,p′-DDE. Parity was a significant predictor of p,p′-DDE. Hg and Pb concentrations increased with increasing age and males had significantly higher concentrations of Pb than women. The study group from Izhma had significantly higher concentrations of Cd when controlling for age and gender and the study group from Usinsk had higher concentrations of Se than the others. Compared to the results from Nelmin-Nos in 2001–2003, a clear decrease in p,p′-DDE concentrations for both women and men was observed.The current study indicates a significant reduction of several PTSs in human blood samples from North West Russia over the past 10 years.